2017
DOI: 10.17755/esosder.298092
|View full text |Cite
|
Sign up to set email alerts
|

Peyzaj Mi̇marliğinda Temel Tasarim Dersi̇ni̇n Öğrenme Ve Yaraticilik Süreci̇ne Etki̇leri̇

Abstract: Temel Tasarım, tasarımla uğraşan bütün disiplinler için özgün, önemli ve zorunlu bir derstir. Bu ders sürecinde öğrenciler, alanlarına dair temel kavramları öğrenirken tasarım öğe ve ilkelerini uygulamalı çalışmalarla kavrarlar. Tasarım bir çeşit sorun çözme eylemi olarak ele alındığında, Temel Tasarım dersi bu eylemin en temel aracı olan yaratıcı düşünmeyi öğrencilere öğretmektedir. Gerçeği ve verilen sorunu analiz etmek, kavramsal olarak parçalarına ayırmak, fikir üretmek ve somut yaratıcı bir sonuca varabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This difference makes it difficult for students to learn design process and produce unique projects in studio courses. Many researchers state that the students receiving Interior Design education mostly have difficulty in studio courses in the first year when the design process is learned [1][2][3][4][5][6][7][8]. Another reason for this difficulty is the formal education system they were previously used to [9].…”
Section: Gamification and Interior Architecture Educationmentioning
confidence: 99%
“…This difference makes it difficult for students to learn design process and produce unique projects in studio courses. Many researchers state that the students receiving Interior Design education mostly have difficulty in studio courses in the first year when the design process is learned [1][2][3][4][5][6][7][8]. Another reason for this difficulty is the formal education system they were previously used to [9].…”
Section: Gamification and Interior Architecture Educationmentioning
confidence: 99%
“…He suggested that students can increase their success by being aware of their learning styles and internalizing their advantages and disadvantages. Düzenli et al (2017) asked landscape architecture students to design a building environment in the last weeks of the basic design course, and as a result of the evaluations made at the end of the study, they observed that the basic design course increased creativity in design studies. Kasap and Türkmen (2018) evaluated form production in the transition from two-dimensional works to volumetric works in the basic design course, through student works.…”
Section: Introductionmentioning
confidence: 99%
“…The landscape designs are shaped by considering the topography of the area to be designed, the structural elements on it, the desires of the users if there is any and the functionality of the area (Düzenli et al, 2017). The shape and function of the space is very influential in the design of the space.…”
Section: Introductionmentioning
confidence: 99%